Agro-Industrial Waste from Cocoa Pod Husk (Theobroma cacao L.), as a Potential Raw Material for Preparation of Cellulose Nanocrystals (2022)
Obtaining cellulose from agro-industrial waste offers the possibility of generating added value to solid biomass that is currently deposited in sanitary landfills. This research performed the evaluation of a residue from cocoa husk pods (Theobroma cacao L.), from the agricultural industry. The cellulose fiber was obtained through chemical treatments with KOH at 5% w/v to remove non-cellulosic components and then the fiber was bleached with 3% v/v hydrogen peroxide. The changes in chemical structure were determined through Fourier transform infrared spectroscopy (FTIR). The FTIR analysis confirms the progressive decrease of lignin and hemicellulose after applying chemical treatment. The morphological changes in the surface of the fiber were characterized using the SEM technique. The mass percentage of cellulose increases up to 68 %. It is expected that the Nano Crystals (NCC) extracted from the biomass of the cocoa husk pods, present a high index of crystallinity and that they are also in suitable conditions to be useful as reinforcing agents in polymeric or mineral matrices, and may have potential application for technology transfer.